Human body modifications and transformations in remaining human and the future of nursing practice - Pepito, Joseph Andrew; Lim-Saco, Freslyn; Moreno-Lacalle, Rainier; Juntasopeepun, Phanida; Constantino, Rose; Rivera, Reynaldo; Locsin, Rozzano C. (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
People strive to remain ‘human,’ even when facing biological traits they see as ‘non-characteristic.’ Oftentimes, this fundamental drive leads individuals to use technology for self-change and improvement, aiming to realize their authentic sense of self. In this paper, we undertake a discursive, concept-driven inquiry to explore how the pursuit of completeness through body modification influences what it means to ‘remain human’ and how this, in turn, shapes the future of nursing. Drawing from a posthumanist framework that integrates the philosophies of Braidotti, Deleuze, and Heidegger with the nursing theories of Parse, Locsin, and Boykin & Schoenhofer, we argue that this technological transformation is a profound process of ‘becoming.’ Our analysis, informed by a purposive review of relevant literature, suggests that in a technology-rich world, nursing faces new opportunities that demand refined practices. To remain relevant, the nursing profession must adapt to these ongoing human transformations by expanding its understanding of personhood and human care.